2003
DOI: 10.1001/archpsyc.60.5.497
|View full text |Cite
|
Sign up to set email alerts
|

The Heritability of Bipolar Affective Disorder and the Genetic Relationship to Unipolar Depression

Abstract: As defined by the DSM-IV, BPD is highly heritable. There are substantial genetic and nonshared environmental correlations between mania and depression, but most of the genetic variance in liability to mania is specific to the manic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
668
3
18

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,116 publications
(721 citation statements)
references
References 21 publications
24
668
3
18
Order By: Relevance
“…Intriguingly, a recent twin study suggests that the genetic vulnerability for mania and depression, although related, is separable (McGuffin et al, 2003). It is important to distinguish depression from mania in studies of psychosocial predictors (Johnson and Kizer, 2002) and neurotransmitter correlates (Joffe, Young, & MacQueen, 1999).…”
Section: Polarity-specific Effectsmentioning
confidence: 99%
“…Intriguingly, a recent twin study suggests that the genetic vulnerability for mania and depression, although related, is separable (McGuffin et al, 2003). It is important to distinguish depression from mania in studies of psychosocial predictors (Johnson and Kizer, 2002) and neurotransmitter correlates (Joffe, Young, & MacQueen, 1999).…”
Section: Polarity-specific Effectsmentioning
confidence: 99%
“…However, despite phenotypic aggregation within families [McGuffin et al, 2003; Lichtenstein et al, 2009], no studies have so far examined polygenic risk incorporating these common genetic factors in a family context in adults, with only one group to date reporting on polygenic risk in adolescent offspring of individuals with BP [Whalley et al, 2012, 2013]. …”
Section: Introductionmentioning
confidence: 99%
“…1 Twin, family and adoption studies have suggested that genetic factors are involved in BD, but no causal mutation has yet been identified. 2 The identification of susceptibility genes has been hampered by a lack of consensus concerning the most valid phenotype to investigate and by the unknown genetic validity of the classical clinical classifications. To disentangle the genetic and clinical heterogeneity of the disorder, a clinical approach based on candidate symptoms has been proposed.…”
Section: Introductionmentioning
confidence: 99%